Experimental investigation on the fiber preform deformation due to mold closure for composites processing - Dong, Jonathan (Springer, 2014)
In liquid composite molding processes, e.g., resin transfer molding, fiber preforms deform when mold is closed. This deformation of fiber preform due to mold closure causes inconsistencies to the permeability, and thus has a negative impact on resin flow. The variations in resin flow cause defects, e.g., dry spots and voids, resin-rich surfaces/zones, fiber distortions, which result in large variations in the product dimensions and mechanical performance. Thus, good understanding of the effects of process parameters on the deformation of fiber preform is necessary for developing high-quality affordable composites. An experimental study on the deformation of fiber preform for making angle-shaped composite parts is presented in this paper. The effects of enclosed angle, radius, fiber volume fraction, and stacking sequence were studied efficiently using design of experiments (DOE). Two open-channel molds were designed and fabricated for varying the design parameters. In each experiment run, the fiber preform was loaded into the mold and the mold was closed. The gaps formed between the fiber preform and inner mold surface were visually inspected by a microscope, and quantitatively characterized. The data were then analyzed. It is shown from the experiments that gaps occur at two locations: at corner radii and beside corner radii. The following conclusions are drawn from this experimental study: (1) fiber volume fraction is the most significant factor affecting the gaps at corner radii, and the gap thickness decreases with increasing fiber volume fraction; (2) the gap thickness decreases with increasing radius; and (3) the gap thickness of unidirectional preforms is larger than that of the cross-ply preforms.